2020
DOI: 10.21037/atm.2020.02.185
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nomogram for lymph node metastasis in pathological T1 esophageal squamous cell carcinoma: a multicenter retrospective study

Abstract: Background: Endoscopic resection is increasingly used to treat pathological T1 (pT1) esophageal cancer (EC) patients. However, the procedures are limited by lymph node metastasis (LNM) and remain controversial. We aimed to construct a nomogram to predict the risk of LNM in patients with pT1 esophageal squamous cell carcinoma (ESCC). Methods: A total of 243 patients with pT1 ESCC who underwent esophagectomy and lymph node dissection at two different institutes between February 2013 and June 2019 were analyzed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Three[ 13 - 15 ] were multicenter studies, and fourteen[ 16 - 29 ] were single-center studies. All studies were conducted in Asian countries, including seven in China[ 14 , 15 , 20 , 21 , 23 , 26 , 29 ], seven in Japan[ 16 , 18 , 19 , 22 , 24 , 27 , 28 ] and three in South Korea[ 13 , 17 , 25 ]. All patients underwent open esophagectomy/thoracoscopy-assisted esophagectomy/ER and 2- or 3-field lymphadenectomy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three[ 13 - 15 ] were multicenter studies, and fourteen[ 16 - 29 ] were single-center studies. All studies were conducted in Asian countries, including seven in China[ 14 , 15 , 20 , 21 , 23 , 26 , 29 ], seven in Japan[ 16 , 18 , 19 , 22 , 24 , 27 , 28 ] and three in South Korea[ 13 , 17 , 25 ]. All patients underwent open esophagectomy/thoracoscopy-assisted esophagectomy/ER and 2- or 3-field lymphadenectomy.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3775 patients were enrolled, of whom 914 had LNM and 2861 were non-LNM, with a metastasis rate of 24.2%. In terms of the assessment of the Newcastle-Ottawa Scale, 11 studies[ 8 , 13 , 16 - 22 , 25 , 27 ] scored 6, and 6 studies[ 14 , 15 , 23 , 24 , 26 , 28 ] scored 7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also found that the coexistence of multiple diseases could significantly reduce the quality of INR control in AF patients receiving warfarin (Davis et al, 2005;Apostolakis et al, 2013), which can be explained by the increased number of hospitalizations required each year due to the Thromboembolic events, n (%) 3 (5.3%) 11 (5.3%) 1.000 Ischaemic stroke, n (%) 3 (5.3%) 9 (4.3%) 0.725 Myocardial infarction, n (%) 0 (0.0%) 1 (0.5%) 1.000 Peripheral venous thrombosis, n (%) 0 (0.0%) 1 (0.5%) 1.000 Bleeding events, n (%) 2 (3.5%) 9 (4.3%) 1.000 Epistaxis, n (%) 1 (1.8%) 0 (0.0%) 1.000 Hemoptysis, n (%) 0 (0.0%) 1 (0.5%) 0.251 Haematuria, n (%) 0 (0.0%) 3 (1.4%) 1.000 Gastrointestinal haemorrhage, n (%) 0 (0.0%) 3 (1.4%) 1.000 Subcutaneous hemorrhage, n (%) 1 (1.8%) 1 (0.5%) 0.385 Subconjunctival hemorrhage, n (%) 0 (0.0%) 1 (0.5%) 0.251 comorbidities, which, in turn, led to poor anticoagulation quality in AF patients receiving warfarin. Nomogram, as a graphical model calculating the probability of the outcome, has been improved as a feasible model in risk prediction and has been widely used in recent years (Lei et al, 2016;Serenari et al, 2020;Tian et al, 2020). To our knowledge, this study is the first to explore a feasible nomogram for predicting anticoagulation quality in Chinese AF patients receiving warfarin.…”
Section: Prediction Model Of Anticoagulation Qualitymentioning
confidence: 98%